Different preferences for wine communication - Sandro Sillani; Alessandra Miccoli; Federico Nassivera (Wine Economics and Policy, 2017)
This study aimed at verifying the presence of variations in the reactions of different types of audiences to certain communication tools for wine. Five samples of audiences were compared: wine professionals, organic produce specialists, wine tourists, and two samples of general tourists. The following bundle of attributes were considered: name of the grape; information on organic production methods; type of closure; QR code; landscape; advertising language. Diverse audience’s preferences were measured by conjoint analysis. The results have shown a common sensitivity to certain attributes, and a different or contrary sensitivity to others. In particular, all samples have demonstrated that: 1) certified organic wines communicated in standard wine-market style have the potential of becoming market leaders; 2) photographs facilitate the acceptance of technologically-advanced closures; 3) the presence of the QR code in printed advertisements increases the expected value of the product; 4)a landscape characterised by holistic “garden viticulture” increases preferences. Textual language was more effective with professionals, while photographic language was more effective with tourists. Supplementary information on the organic production methods, in addition to the mandatory labelling requirements, increased the preferences of professionals and wine tourists, and was counterproductive with the general tourists.